PENGABDIAN MASYARAKAT BERBASIS POTENSI (PMBP) BIMBINGAN SERTA PELATIHAN DALAM SKILL POTENSI ANAK- ANAK DALAM PUCBLIK SPICKING MENGGUNAKAN BAHASA INDONESIA YANG BAIK DAN BENAR DI SMP KERTANEGARA MALANG - Vika Ira Prameswari; Muhammad Amru Ashodiki; Kingkin Puput Kinantu; Lis Susilawati; Susandi (Inspirasi: Jurnal Pengabdian Masyarakat, 2025)
Potential-Based Community Service (PMBP) is a community service program. Public speaking is the ability to speak in public to convey delivery and adjusting the style of speech to the audience. Public speaking is not just about speaking. I conducted this research at SMP Kertanegara Malang middle school for 2 month for my aticle reseach at the end of this semester. This research is to develop student appleal to be confident when public speaking in public.i set the child’s metal to become a strong and confident soul when showingthe results he has made in front ogf his friends.